Rapid diffused optical imaging for accurate 3D estimation of subcutaneous tissue features - Shanshan Cai; John Mai; Winn Hong; Scott E. Fraser; Francesco Cutrale (iScience)
Summary: Conventional light imaging in living tissues is limited to depths under 100 μm by the significant tissue scattering. Consequently, few commercial imaging devices can image tissue lesions beneath the surface, or measure their invasion depth, critical in dermatology. We present 3D-multisite diffused optical imaging (3D-mDOI) an approach that combines photon migration techniques from diffuse optical tomography, with automated controls and image analysis techniques for estimating lesion’s depth via its optical coefficients. 3D-mDOI is a non-invasive, low-cost, fast, and contact-free instrument capable of estimating subcutaneous tissue structures volumes through multisite-acquisition of re-emitted light diffusion on the sample surface. It offers rapid estimation of Breslow depth, essential for staging melanoma. To standardize the performance, 3D-mDOI employs customized calibrations using physical tissue phantoms, to explore the system’s 3D reconstruction capabilities. We find that 3D-mDOI can reconstruct lesions up to 5 mm below the surface, requiring ∼300 s of computation time.